Peran Self-Efficacy sebagai Variabel Intervening dalam Hubungan antara Workplace Training dan Pengembangan Profesional terhadap Kinerja Karyawan di KTU Shipyard Batam - Putri Wahyuni; Mira Yona; Difa Sobri; Rita Indriani; Linda Rosiyanti; Andika Pratama (CV. ITTC INDONESIA, 2026)
In the dynamic era of business competition, organizations are required to continuously improve the quality of human resources through various development programs. Two factors often associated with performance improvement are workplace training and professional development. This study aims to analyze the role of self-efficacy as an intervening variable in the relationship between workplace training and professional development on employee performance at KTU Shipyard Tanjung Uncang Batam. The study involved 30 employees selected through purposive sampling technique. This research employs a quantitative approach with a purposive sampling technique. The sample size in this study was 30 respondents. Data processing methods included validity and reliability tests to assess the feasibility of the research instruments, followed by classical assumption tests consisting of normality and multicollinearity tests. Subsequently, multiple linear regression analysis, F-test, t-test, coefficient of determination, and mediation tests were conducted to address the research hypotheses. The results show that simultaneously, workplace training and professional development have a significant effect on employee performance F = 25.507; p = 0.000. Partially, only self-efficacy has a significant effect on employee performance t = 3.469; p = 0.002. The mediation test indicates that self-efficacy does not act as an intervening variable; instead, employee performance significantly affects self-efficacy t = 3.469; p = 0.002. This finding suggests a reciprocal relationship that warrants further investigation. The managerial implication emphasizes the importance of directly strengthening self-efficacy to enhance employee performance.